DISTANCE LEARNING / TEACHING CURRICULUM DESIGNING MODEL IN THE PERSPECTIVE OF QUALITY ASSESSMENT DIMENSIONS AND FACTORS - Laužackas †, Rimantas; Teresevičienė, Margarita; Volungevičienė, Airina (Acta Paedagogica Vilnensia, 2009)
The article addresses the problem that distance learning / teaching curriculum designers do not apply distance learning / teaching curriculum designing theories, and they do not estimate the needs of distance learning / teaching organization process. The majority of factors influencing distance learning / teaching curriculum quality are theoretically supported, but they are not applied by distance learning / teaching curriculum authors in Lithuania.The aim of the research is to prepare distance learning / teaching curriculum designing model on the basis of distance learning / teaching curriculum quality assessment factors and dimensions.The authors reveal the importance of distance learning / teaching curriculum designing quality assessment dimensions for distance learning/ teaching curriculum designing in the first part of the article. Distance learning / teaching curriculum quality assessment factors are identified in the second part of the article and they are correlated with the learning / teaching strategy consistency dimension. The last part is dedicated to present the model of distance learning / teaching curriculum designing, based on quality assessment factors.The conclusions of the research present consistent results with the theoretical parts of the paper: the importance of the dimesnion of distance learning/ teaching curriculum quality assessment for distance learning/ teaching curriculum designing, their interrelation with quality assessment factors, as well as their integration into distance learning / teaching curriculum designing model.
Keywords: distance learning / teaching curriculum quality assessment dimensions; distance learning / teaching curriculum quality assessment factors; distance learning / teaching curriculum designing model